Assessing Changes in Quality and Quantity of Entering Stream to Hor-Al-Azim Wetland Regarding Karkhe Dam Construction - Samira Foladvand; Gholamabbas Sayad; Kazem Hemadi; Hadi Moazed (علوم و مهندسی آبیاری, 2014)
Hor-Al-Azim wetland is located in southwestern of Khuzestan province in Iran in the Iran-Iraq border. In 1377و Iran started to use the biggest dam on the Karkeh river. This river is one of the largest water sources of Hor-Al-Azim wetland. The dam is designed to irrigate 32000 hectares of lands in Khuzestan plain. This study was conducted to evaluate changes in the quality and quantity of entering water into the wetland due to Karkhe dam construction and also precipitation change using long time data. The required data was collected from three hydrometric stations in the Karkheh watershed including Hufl, Nissan, and Hamidieh. Data analysis showed significant differences between quantitative and qualitative parameters of Karkheh river in Hamidieh hydrometric stations in the periods before and after the Karkheh dam construction. The results showed that the lower quantity and quality of the entering water to the wetland for these years was due to combine effects of lower participation rate and also reducing flow rate as a consequence of dam construction.